COVID-19 pandemic : lessons from the frontline - Hidalgo, Jorge; Rodríguez-Vega, Gloria; Pérez Fernández, Javier (Elsevier, 2022)
Providing a broad, global view of all aspects related to preparation for and management of SARS-CoV2, COVID-19 Pandemic: Lessons from the Frontline explores and challenges the basis of knowledge, the transmission of information, and the preparation and epidemiology tactics of healthcare systems worldwide.